1995
DOI: 10.1159/000217177
|View full text |Cite
|
Sign up to set email alerts
|

Increased Concentrations of Tumor Necrosis Factor and lnterleukin-6 Contribute to the Hemostatic Abnormalities in Advanced Liver Disease

Abstract: Abnormal cytokine levels have been described in patients with chronic liver disease, but studies correlating cytokine homeostasis with abnormalities in coagulation and fibrinolysis are lacking. In order to establish a link between cytokines and the hemostatic changes the following parameters were determined in 44 patients with cirrhosis (alcoholic =15, postnecrotic = 22, others = 7): TNF-α, IL·6, thrombin-antithrombin (TAT) complexes, prothrombin fragment 1 + 2 (F1 + 2) and t-PA by using enzyme-linked immunoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Furthermore, TAT and AT were the only coagulation parameters to be independently associated with liver function impairment. Our findings are similar to that reported by other groups 7,8,19–21 reinforcing the existence of a hypercoagulable profile in patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, TAT and AT were the only coagulation parameters to be independently associated with liver function impairment. Our findings are similar to that reported by other groups 7,8,19–21 reinforcing the existence of a hypercoagulable profile in patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 93%
“…18 The TAT assay has been frequently employed in the published work as a laboratory index to excessive TG in patients with cirrhosis. [19][20][21][22] A marked increase in TG together with a depressed anticoagulant activity was noted in patients with cirrhosis compared with normal subjects. Interestingly, TAT levels were elevated even in Child-Pugh A patients compared with controls in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been suggested that bacterial infections and endotoxemia may be important triggers of variceal bleeding in cirrhosis (21). Endotoxemia has been proven to be a powerful activator of clotting and fibrinolysis in liver cirrhosis (19,22).…”
Section: Clinical Studies Of Endotoxin and Cytokines In Hepatic Inflamentioning
confidence: 99%
“…In observational studies in various patient populations including healthy individuals, patients at high cardiovascular risk as well as in patients with advanced liver disease [36-39] IL-6 levels have been shown to correlate with tPA, which supports IL-6 induced endothelial cell activation and subsequent release of tPA as one of the potential underlying pathways [40]. In experimental models IL-6 also induced the expression of plasminogen, which is a substrate for plasmin [41].…”
Section: Discussionmentioning
confidence: 99%